ANALISIS KEMANDIRIAN BELAJAR SISWA SELAMA PANDEMI COVID-19 DI DESA SOSORGONTING KECAMATAN ANDAM DEWI - Ramli Simatupang; Zulfadli Nasution; Eva Yanti Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
Abstract The background of this research is the emergence of the Covid-19 pandemic at the beginning of 2020 and this is a year that worries all countries, including Indonesia. This pandemic also occurred in Indonesia which made many parties participate in overcoming this pandemic. Learning in Sosorgonting village of Adam Dewi sub-district had carried out learning at home to avoid physical contact with others. The purpose of this study was to find out how students’ learning independent was during the Covid-19 pandemic in Sosorgonting village, Andam Dewi sub- district. The research method used is descriptive quantitative. The instrument used is a questionnaire with 15 students as respondents. The results showed 3 students had average 84 (very good category), 11 students had average 71.2 (good category), 1 student had average 53.3 (poor category) Keywords: Independent learning, learning mathematics, Covid-19